Unleashing resistance and decoding the backstories behind six: a post-structural reading of selected digital six-word memoirs - Neval Nabil Abdullah (Insights into Language, Culture and Communication)
The present paper is mainly concerned with exploring an intriguing minimalist literary genre, known as the digital ‘six-word memoir.’ A captivating form of artistic expression, this succinct format is a realm whose brevity and timeliness uniquely suits online platforms and remarkably aligns with the preferences of contemporary readers amidst information overload. Transcending its brevity to become a catalyst for reflection, the six-word memoir manages to encapsulate stories of defiance and resilience, displaying the capacity of individuals to stand up for what is right and to fight for what are theirs. For this purpose, the present study embarks on navigating the contours of this genre and exploring the interplay of form and content in selected thought-provoking digital six-word memoirs, weaving threads of personal and collective resistance. Highlighting the subversive power dynamics embedded within the brevity of each snippet, the study demonstrates the way each condensed story, through a deliberate selection and careful arrangement of words, taps into a contentious issue, distills a social commentary, and encapsulates a different aspect of resistance – be it a tale of personal struggle, a call for societal transformation, or a pursuit of justice. As such, the study draws on the 'Post-structural Approach’ as it highly resonates with the brevity and depth of the self-contained, counter narratives under consideration and serves the purpose of the study. Received: 24 July 2024 Accepted: 19 September 2024 Published: 03 October 2024